ORIENTATION AND HOUSE PLAN CONFIGURATION FOR ENERGY CONSERVATION IN LAHORE - S. Arif, (Pakistan Journal of Science, 2022)
This research focuses on energy conservation giving emphasis on Passive design application in residential buildings of government and private sectors with respect to solar orientation. The environmental data are calculated and presented for the solar passive application in architectural and urban designing for thermal control. The study is based on the experimental findings of test rooms at main orientations and the results are applied on a standard house plan configuration for the validity. The results showed the SW an optimum orientation for heating and cooling requirements for energy conservation.